2020
DOI: 10.1111/ajt.15631
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T cells promote corneal endothelial cell survival following transplantation via interleukin-10

Abstract: | INTRODUC TI ONCorneal transplantation is the most common form of tissue grafting worldwide. 1 When performed on an uninflamed and nonvascularized host bed, the graft survival rate exceeds 90%. 2 However, inflammation and vascularization of the host bed disrupt the cornea's relatively tolerant immune microenvironment, and graft survival rates fall to ≈50% despite maximum immunosuppression in highrisk recipients. 3-5 Immune rejection is the leading cause of corneal graft failure. 6 Corneal endothelial cells (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…Treatment with T regulatory cells (Tregs) or tolerogenic APCs induced by immunoregulatory factors can help restore immune privilege and thus lead to the longterm survival of the corneal allograft in high-risk recipients. Host alloimmunity is the main cause of loss of donor CEnCs after corneal transplantation [106]. Tregs play a critical role in suppressing immune responses after tissue transplantation.…”
Section: Immune Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment with T regulatory cells (Tregs) or tolerogenic APCs induced by immunoregulatory factors can help restore immune privilege and thus lead to the longterm survival of the corneal allograft in high-risk recipients. Host alloimmunity is the main cause of loss of donor CEnCs after corneal transplantation [106]. Tregs play a critical role in suppressing immune responses after tissue transplantation.…”
Section: Immune Cellsmentioning
confidence: 99%
“…This function is significantly compromised in Tregs derived from high-risk hosts. The cytoprotective role of Tregs is mediated by the immunomodulatory cytokine IL-10; hence, IL-10 is effective in protecting CEnC from inflammatory cytokines during cell death [106].…”
Section: Immune Cellsmentioning
confidence: 99%
“…Interestingly, Coco et al demonstrated a protective role of Tregs directly on epithelial cells of the cornea. Combination of mouse model of corneal transplantation and in vitro experiments imitating proinflammatory environment of the rejection process showed superior capacity of acceptors' Tregs to produce IL-10 [ 102 ].…”
Section: Future Directions For Improving Corneal Transplantation Outcomesmentioning
confidence: 99%
“…To evaluate the cytoprotective function of Tregs, a cornea-in-thecup assay was performed and optimized as described previously. 21 Briefly, cornea cups from normal BALB/c mice were cultured with Tregs in complete RPMI-1640 medium with or without recombinant mouse IFNγ (100 ng/mL, Preprotech) and TNFα (100 ng/mL, Preprotech) for 12 h at 37°C. After incubation, cornea cups were washed with PBS and then fixed in 4% paraformaldehyde for 15 min at room temperature.…”
Section: Cornea-in-the-cup Assaymentioning
confidence: 99%